Construct Validity Testing of Hatred Scale Using Confirmatory Factor Analysis - Gazi Saloom; Muhammad Nurrifqi Fuadi (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2021)
This research was conducted to test the construct validity of hatred. This research uses two hatred dimensions from Halperin et al., (2012), namely chronic hatred and immediate hatred with a total of 13 items. Data obtained from 361 students of UIN Syarif Hidayatullah Jakarta. The analytical method used in this study is Confirmatory Factor Analysis (CFA) with the help of the lisrel program. The results of this study indicate that all items are unidimensional. This means that all items only measure one factor so that the one-factor model theorized in the hatred can be accepted.